Kajian Aksiologi terhadap Teknik Cryonics sebagai Solusi Menuju Kehidupan Kedua - Kadek Dwi Hendratma Gunawan (Jurnal Filsafat Indonesia, 2018)
Improving science and technology is done to eliminate human boundaries and achieve happiness. The death that leads to grief tries to overcome. The concept of immortality is finally born from cryonics techniques. Using the library research method analyzed that, the cryonics technique provides an opportunity to live again in the future, after the death of an incurable illness today. But this technique is contrary to the ethical and aesthetic aspects of Indonesia. The belief in God is shaken by its incompatibility with the potentialities of the cryonics technique. The shift in the meaning of death both scientifically and legally needs to be reexamined. A view of the axiological study of cryonics techniques needs to be studied in more depth, especially so as not to become a problem in the future.